Corporate social responsibility strategies in Nigeria: a tinged shareholder model. Issue 5 (13th May 2020) - Adegbite, Emmanuel; Amaeshi, Kenneth; Nakpodia, Franklin; Ferry, Laurence; Yekini, Kemi C.
Abstract : Purpose: This paper aims to examine two important issues in corporate social responsibility (CSR) scholarship. First, the study problematises CSR as a form of self-regulation. Second, the research explores how CSR strategies can enable firms to recognise and internalise their externalities while preserving shareholder value. Design/methodology/approach: This study uses a tinged shareholder model to understand the interactions between an organisation's CSR approach and the effect of relevant externalities on its CSR outcomes. In doing this, the case study qualitative methodology is adopted, relying on data from one Fidelity Bank, Nigeria. Findings: By articulating a tripodal thematic model – governance of externalities in the economy, governance of externalities in the social system and governance of externalities in the environment, this paper demonstrates how an effective combination of these themes triggers the emergence of a robust CSR culture in an organisation. Research limitations/implications: This research advances the understanding of the implication of internalising externalities in the CSR literature in a relatively under-researched context – Nigeria. Originality/value: The data of this study allows to present a governance model that will enable managers to focus on their overarching objective of shareholder value without the challenges of pursuing multiple and sometimes conflicting goals that typically create negative impacts to non-shareholding stakeholders.